Teaching the history of economic thought integrating historical perspectives into modern economics - Tavasci, Daniela; Ventimiglia, Luigi (Cheltenham, UK Northampton, MA, USA EE, Edward Elgar Publishing, 2018)
Stemming from the idea that economics is a social science that tends to forget its own history, this refreshing book reflects on the role of teaching with historical perspectives. It offers novel ways of integrating the history of economics into the curriculum, both in history of economic thought modules and in other sub-disciplines. Coming from a wide diversity of experiences, the contributors explore the idea that studying the history of thought exposes students to pluralism, and that it is therefore an essential pedagogical tool. They also argue that this method of teaching will reveal the historical contextualisation of current theories and show how they are the results of a specific evolution within the discipline. Ultimately, this book demonstrates how some modules have successfully operationalized both the history of economic thought and the teaching of various sub-disciplines from a historical perspective.
"THP matters : teaching with historical perspectives"--Cover.
Keywords: Economics -- History -- Study and teaching (Higher); Economics -- Study and teaching (Higher); History